Struktur Sosial dan Pemerintahan Pada Masa Kesultanan Palembang Darussalam - Muhammad Reza Arviansyah (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2021)
The Sultanate of Palembang Darussalam, an Islamic sultanate that stands in the city of Palembang, has a territory that is widely traversed by rivers that stretch and interconnected but still boils down to the musi river as the center of government this is also what makes the majority of all people's life activities are on the banks of the river. People's lives here are also fairly orderly with the Simbur Cahaya Law that governs the entire order of life and is used by the Sultanate of Palembang as a guideline of the applicable law. Whether it applies to residents in the center of the capital (iliran) or to control the residents in the hinterland (uluan), in practice the Sultan has several princes and other officials to help run the government structure and appoint the person he trusts as the length of the sultan's hand so as to create order in the running of government and social conditions This data collection is done with various analysis of the existing written evidence while paying attention to the similarity between the content and the theme to be raised. This paper will try to raise about how the social situation of society and the condition of the government that took place in the Sultanate of Palembang Darussalam when viewed from an economic and legal point of view that became an advantage for the Sultanate of Palembang. So it is no wonder that later this palembang sultanate area becomes an area that is considered strategic by outside nations.